Analysis of Work Stress Factors Among Young Teachers at Madrasah Ibtidaiyah Swasta No. 20/e.3 Sungai Tutung - Partiwi, Marsa Hijro; Muspawi, Mohammad; Rahman, K.A (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This reserarch aims to analyze the factors contributing to work-related stress among young teachers at Madrasah Ibtidaiyah Swasta (MIS) No. 20/e.3 Sungai Tutung. The research employs a descriptive qualitative method with a case study approach interviews and participatory observation. The findings reveal that work-related stress among young teachers is influenced by several key factors, including high workloads, challenges in classroom management, lack of social support from colleagues, and limited facility conditions. Many young teachers experience difficulties in adapting to job demands and feel isolated due to insufficient guidance from senior teachers. This study underscores the importance of institutional support, including mentoring programs, skill training, and facility improvements, to help young teachers manage stress and enhance their teaching quality. The findings are expected to serve as a reference for school authorities in formulating better policies for teacher welfare.